The impact of strengthening fiqh learning in the department of islamic education through integrating health sciences - Nurkhamidi, Aris; Khuzaiyah, Siti; Widodo, Syukri Fathuddin Ahmad (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2023)
Students majoring in Islamic Education at the Faculty of Tarbiyah and Teacher Training are expected to be competent in understanding and teaching Islamic Religious Education subjects in schools. Among the Islamic Religious Education materials in schools is the Fiqh of worship. Based on field studies, religious fiqh lectures are carried out with a pure fiqh approach. Fiqh lectures have not been integrated with other relevant sciences and disciplines, such as health sciences. This research and development (R&D) aimed to examine the impact of integrated learning between Fiqh and health science on the students. This study was research and development combining the concept of religious fiqh lectures with the health sciences aspect. The respondents were students in the Faculty of Tarbiyah and Teacher Training.  The results showed that integrating Fiqh and Health sciences has positive impacts, namely: (1) increasing student motivation and attention in lectures, (2) increasing mastery of fiqh material from the point of view of health sciences, and (3) improving the readiness of students in pursuing the profession of Islamic religious educators in schools. Three methods that could possibly implement the design of strengthening Fiqh learning with health sciences were (1) Lectures with a single lecturer, (2) lectures with team teaching lecturers, and (3) lectures with additional classes specifically for health sciences (Special session). Integrating fiqh subjects with health sciences could be taken into account, as it might benefit the student's competence in mastering fiqh science on a broader view.